The importance of on-site evaluation for placing renewable energy in the landscape: A case study of the Búrfell wind farm (Iceland) - Frantál Bohumil (Moravian Geographical Reports, 2017)
Using a case study of the Búrfell wind farm project, a large wind farm proposed in the Central Highlands of Iceland, the authors attempt to provide new insights into the factors shaping subjective landscape perceptions and attitudes to renewable energy developments, and into alternative methods that may be used for their assessment. The research was based on an on-site visit and actual experience of the place, investigated using a combination of mental mapping, the technique of the semantic differential and a questionnaire survey. The results show that participants visiting a landscape and using all sensory organs in combination with mental mapping, can reveal more important information than using only ‘laboratory’ methods with static photographs. The results suggest that the perception of landscape is highly subjective. Those perceiving the landscape as more open, homogenous, industrial, unfamiliar and resilient also consider it more compatible with wind turbines. The perception of the landscape’s compatibility with wind turbines proved to be a dominant factor shaping attitudes towards the project. The acceptance of wind turbines is not, however, inconsistent with the perception of landscape as beautiful, wild and unique. Participants from more densely populated countries and countries with a developed wind energy industry were more tolerant of wind turbines in the Icelandic landscape.